Change and continuity in the management model of overseas Chinese family enterprise : a comparative study of six Singaporian Chinese businesses. - Zheng, Qun. (2008)
This paper aims to identify the changing managerial personnel composition of overseas Chinese family businesses and examine the underlying market, cultural or institutional forces. Based on within-case and cross-case study of six Singapore Chinese businesses, the researcher finds that development of the six family businesses follows the same pattern: the transformation from a family-controlled and managed business at founding period to professionally managed yet family controlled one provided that the founding family is still the biggest shareholder of the business per se.